Progressing measurement in mental toughness: A case example of the Mental Toughness Questionnaire 48 - Gucciardi, Daniel; Hanton, S.; Mallett, C. (American Psychological Association, 2012)
Mental toughness has received increasing attention in the field of performance psychology, yet issues remain about its measurement by self-report. In this article, we have summarized mental toughness measurement issues and, as an example, provided a psychometric examination of the most frequently used measure. In an effort to operationalize mental toughness, Clough, Earle, and Sewell (2002) developed the Mental Toughness Questionnaire 48 (MTQ 48) and provided initial evidence for its reliability and validity. Subsequent research has partially supported the internal reliability and validity of the MTQ 48. However, no research has rigorously tested the factorial structure of the hypothesized model underlying this scale. Using two independent samples of performers from various sports (n = 686) and the workplace (n = 639), we sought to examine the factorial validity of the MTQ 48 using confirmatory factor analysis (CFA) and exploratory structural equation modeling (ESEM). Both CFA and ESEM indicated that the hypothesized correlated four factor model did not fit the data well in the athlete and workplace samples. Our overview of measurement issues and empirical case study of the MTQ 48 underscore the importance of having a clearly articulated conceptual underpinning combined with rigorous statistical procedures in attempting to develop a mental toughness inventory.